The presupositions of Peirce’s ethics that influenced Karl Otto-Apel on the construction of the ethic of discourse - Aguiar, Francisco Brandão (2015)
In this article, it will be analyzed how Charles Sanders Peirce’s philosophy influences Karl-Otto Apel’s thinking on the elaboration of his ethic of discourse. We intend to show that Apel understands that Peirce elaborates a transformation on the Kantian transcendental philosophy, by replacing “I think” for “I argument”’, and in this regard, Peirce demonstrated the existence of a mutual intersubjective agreement within the scientific society. In the means that this agreement is mediated by language and is due to the guarantee of the truthfulness of the presuppositions. It is concluded that Apel sees in Peirce an introduction of a minimum ethics that overcomes the methodical solipsism, and is based on the intersubjectivity, making it possible for a mutual agreement that, later, will be the basis for the pragmatical-transcendental foundation of the ethics of discourse.